FORBIS: Formative Feedback dengan Soal Isomorfik sebagai Sarana Pembenaran Pemahaman Konsep Siswa Materi Fluida Dinamis - Fitria Andriana Rahayu; Sentot Kusairi; Dyah Palupi Rohmiati; Ivan Danar Aditya Irawan (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2026)
This study aims to develop computer-assisted FORBIS to facilitate the correction of students' conceptual understanding of dynamic fluid materials. This Research and Development (R&D) project utilized the Plomp development model, involving two physics lecturers and one physics teacher as expert validators. The subjects consisted of 36 eleventh-grade science students (12 male and 24 female students), with 31 students participating in the practicality test and 5 students involved in the effectiveness test. A stratified purposive sampling technique was employed to select the students for the product effectiveness test. The data collection instruments used were questionnaires and interview guides. This research produced a product named Formative Feedback with Isomorphic Multiple-Choice Questions (FORBIS) to help improve students' conceptual understanding and serve as a tool for independent learning. Based on the validity test, the results obtained were 96.5% (highly valid) for isomorphic questions, 95.7% (highly valid) for true-false questions, 96.5% (highly valid) for feedback, and 96.4% (highly valid) for the overall product. The result of the product practicality test by students was 93.9%, falling into the highly practical category. The effectiveness test was conducted through limited interviews with 5 students before and after using the product, which were analyzed using a descriptive-comparative method to determine changes in students' conceptual understanding. The interview results indicated a positive trend toward the improvement of students' understanding of physics concepts after using the product. Accordingly, this research has successfully developed a computer-assisted FORBIS that meets the criteria of being valid and practical, while also indicating a capacity to support students' conceptual understanding based on limited interview results.